2012
DOI: 10.1523/jneurosci.3308-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation of Homer1a Transcription Regulation in Amygdala and Hippocampus with Pavlovian Fear Conditioning

Abstract: The consolidation of conditioned fear involves upregulation of genes necessary for long-term memory formation. An important question remains as to whether this results in part from epigenetic regulation and chromatin modulation. We examined whether homer1a, which is required for memory formation, is necessary for Pavlovian cued fear conditioning, whether it is downstream of BDNF - TrkB activation, and whether this pathway utilizes histone modifications for activity-dependent transcriptional regulation. We init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 52 publications
6
86
0
Order By: Relevance
“…Previous studies manipulating histone acetylation have not consistently found effects on auditory fear, even with systemic infusions of broad-spectrum HAT or HDAC inhibitors. Some of these studies find effects on context, but not auditory fear (Korzus et al, 2004;Mahan et al, 2012;Wood et al, 2005), whereas others find effects on both context and auditory fear (Alarcon et al, 2004;Bredy and Barad, 2008;Chwang et al, 2007;Gao et al, 2010;Guan et al, 2009;Maddox et al, 2013b). Similarly, the effects of systemic HDAC3 inhibition are mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies manipulating histone acetylation have not consistently found effects on auditory fear, even with systemic infusions of broad-spectrum HAT or HDAC inhibitors. Some of these studies find effects on context, but not auditory fear (Korzus et al, 2004;Mahan et al, 2012;Wood et al, 2005), whereas others find effects on both context and auditory fear (Alarcon et al, 2004;Bredy and Barad, 2008;Chwang et al, 2007;Gao et al, 2010;Guan et al, 2009;Maddox et al, 2013b). Similarly, the effects of systemic HDAC3 inhibition are mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation is a fundamental chromatin regulatory mechanism that is dynamically controlled during learning (Levenson et al, 2004;Maddox et al, 2013b;Mahan et al, 2012;Miller et al, 2008) and critically involved in long-term memory formation (Barrett et al, 2011;Bieszczad et al, 2015;Bredy and Barad, 2008;Guan et al, 2009;Maddox et al, 2013b;McQuown et al, 2011a;Vecsey et al, 2007;Wood et al, 2005). Histone acetylation is modulated through two competing classes of enzymes: HATs and HDACs.…”
Section: Introductionmentioning
confidence: 99%
“…(Gupta-Agarwal et al 2012). Similarly, cued fear conditioning as well as BDNF-induced plasticity in cell culture resulted in different patterns of histone PTMs at the homer1 promoter in hippocampal and amygdala neurons (Mahan et al 2012), indicating that the same gene can be differentially regulated by identical stimuli in different regions of the brain. Epigenetic modifications can be further localized to discrete subregions of the hippocampus.…”
Section: Epigenetic Mechanisms Regulate Memory Across Tasks and Brainmentioning
confidence: 99%
“…Importantly, stimulation of ERK signaling (Levenson et al 2004) and treatment with HDAC inhibitors ) produced gene-and histone-specific changes in PTMs, indicating that distinct signaling cascades may establish precise histone codes that correspond to particular types of memory ). Moreover, BDNF activity regulates the consolidation of contextual fear conditioning through alterations of histone-and residue-specific post-translational modifications at the homer1 promoter in the hippocampus and the amygdala (Mahan et al 2012). In addition, nitric oxide (NO) has been implicated in histone acetylation by regulating the dissociation of HDAC2 from CREB-regulated gene promoters (Nott et al 2008;Nott and Riccio 2009) …”
Section: Epigenetic Modifications Are Regulated In Response To Specifmentioning
confidence: 99%
“…Clinical studies provided first evidence that Homer1 is involved in the development of major depressive disorders (Rietschel et al, 2010), whereas preclinical studies describe its importance in anxiety-and depression-related behavior (Szumlinski et al, 2005;Lominac et al, 2005), memory formation , fear (Tronson et al, 2010), and reward-related behaviors (Jaubert et al, 2007;Szumlinski et al, 2004). Furthermore, the activityinduced splice variant Homer1a (Brakeman et al, 1997) has been shown to be crucially involved in behavioral alterations that are related to depression (Celikel et al, 2007;Mahan et al, 2012) and anxiety . Moreover, prenatal stress was shown to alter Homer1a and Homer1b/c expression in several corticolimbic structures, including the hippocampus (Ary et al, 2007).…”
Section: Introductionmentioning
confidence: 99%